Investigating the ultrastructure of fibrin networks, platelets and coagulation profiles in healthy individuals - Pretorius, Etheresia (University of Pretoria, 2013)
Dissertation (MSc (Anatomy: Cell Biology))--University of Pretoria, 2011.